Prognostic Stratification of Metastatic Prostate Cancer Patients Treated With Abiraterone and Enzalutamide Through an Integrated Analysis of Circulating Free microRNAs and Clinical Parameters - Sharova, Evgeniya; Maruzzo, Marco; Del Bianco, Paola; Cavallari, Ilaria; Pierantoni, Francesco; Basso, Umberto; Ciminale, Vincenzo; Zagonel, Vittorina (Frontiers in Oncology, 2021)
Androgen Receptor-Targeted Agents (ARTA) have dramatically changed the therapeutic landscape of metastatic Castration-Resistant Prostate Cancer (mCRPC). However, 20-40% of mCRCP patients progress early after start of ARTA treatment, and prostate-specific antigen (PSA) “per se” is not a reliable marker of response. The present study investigated the potential utility of plasma cell-free microRNAs (cfmiRNAs) as predictive markers of response to ARTA therapy by analysing a prospective cohort of 31 mCRCP patients treated with abiraterone (N = 10) or enzalutamide (N = 21). Potential prognostic factors were extracted from clinical records and outcome was evaluated as overall survival (OS) and progression-free survival (PFS). cfmiRNAs were measured in plasma samples using quantitative real-time RT-PCR. Linear correlation among clinical factors and cfmiRNAs was assessed using the Spearman’s rank correlation coefficient. The association with survival was studied using univariate and multivariate Cox proportional hazards models. Continuous variables were dichotomized with the cut points corresponding to the most significant relation with the outcome. Univariate analysis indicated that plasma levels of miR-21-5p, miR-141-3p and miR-223-3p, time to development of castration-resistance (tCRPC), and haemoglobin (Hb) levels strongly correlated with both PFS and OS. Multivariate analysis revealed that low plasma levels of miR-21, shorter tCRPC, and lower Hb values were independent factors predicting reduced PFS and OS. These findings suggest that the integrated analysis of cfmiRNAs, tCRPC, and Hb may provide a promising, non-invasive tool for predicting response of mCRCP patients to ARTA.